2022
DOI: 10.5336/nurses.2021-82273
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Acceptance and Hesitancy Among Nurses

Abstract: Aşılama, birçok hastalığa karşı korumanın en basit, etkili, güvenli ve ucuz yoludur. Bir toplumda ne kadar fazla insan aşılanırsa o kadar az insan sa-vunmasız hâle gelir ve enfekte bir kişinin patojeni başka bir kişiye geçirme olasılığı da o kadar azalır. Dünya Sağlık Örgütü (DSÖ) aşılama çalışmaları ile

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…A number of studies have found that vaccine hesitancy is inversely related to education levels among general health workers (Verger & Dubé, 2020; Wilson et al., 2020; Yaqub et al., 2014). Another study also found there is no correlation between nurses' education level and COVID‐19 vaccine acceptance (Çatıker et al., 2022). Regarding this, inadequate research has been conducted regarding the relationship between nursing professionals' educational level and vaccine acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have found that vaccine hesitancy is inversely related to education levels among general health workers (Verger & Dubé, 2020; Wilson et al., 2020; Yaqub et al., 2014). Another study also found there is no correlation between nurses' education level and COVID‐19 vaccine acceptance (Çatıker et al., 2022). Regarding this, inadequate research has been conducted regarding the relationship between nursing professionals' educational level and vaccine acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Sağlık çalışanlarının COVID-19 aşısına ilişkin görüşlerinin incelendiği ve 23 ülkeyi kapsayan çalışmada, sağlık çalışanlarının aşı tereddüdünün olabileceği ve çevrelerini etkileyebilecekleri belirtilmektedir. 31 Türkiye'de Sağlık Bakanlığı ve Türk Ta-bipler Birliği gibi kurumlar resmî sitelerinde gebelere yönelik COVID-19 aşısı ile ilgili bilgilendirme yapmaktadır ve gebelere COVID-19 aşısını yaptırmaları önerilmektedir. 17,22 Ancak bireysel görüşler sorulduğunda sağlık çalışanları arasında da COVID-19 aşısına yönelik fikir birliğinin olmadığı görülmektedir.…”
Section: Bulgularunclassified
“…17,22 Ancak bireysel görüşler sorulduğunda sağlık çalışanları arasında da COVID-19 aşısına yönelik fikir birliğinin olmadığı görülmektedir. [29][30][31] Bu durumun da gebelerin aşı okuryazarlığını ve aşı ile ilgili karar verme sürecini etkilemiş olabileceği düşünülmektedir.…”
Section: Bulgularunclassified